Ownership of Management as a Moderating of Impact Profitability to Firm Value - Aprih Santoso; Nurhidayati Nurhidayati (Universitas Medan Area, 2022)
The rsearch to test the moderation of management ownership to impact profitability to firm value. Data used is secondary data. Population is manufacturing companies whose shares are on IDX during 2016-2020. The advantage of sampling with data pooling is that by obtaining a larger number of samples, it is hoped that it will increase the strength of the test. The sampling technique in this study used purposive sampling: Manufacturing companies with ownership composition shares, which are owned by management in the firm with a total of more than 1% of the total outstanding shares. Firm value is influenced by profitability, if profitability increases, it will have an impact to increasing firm value. Management ownership is proven not to moderate the impact of profitability to firm value, that impact profitability on firm value is not significantly strengthened by the interaction of management ownership variables so that management ownership is not a moderating in interaction profitability to firm value. Firm value will increase, influence of profitability to firm value can lead to positive sentiment for investors, investors managers should continue to work hard, so the firm value can increase.